Linguistics and mathematics meaning - Maanu, Vivian; Asare, Bright (Frontiers in Education, 2025)
This study examines the increasing relationship between linguistics and mathematics education, highlighting how language influences the comprehension and communication of mathematical concepts. It explores how semantics, syntax, discourse, and metaphor influence comprehension, especially in multilingual classrooms where students face challenges due to language differences. Drawing on global research from 2017 to 2025, it emphasizes the role of classroom discourse, sociocultural theory, and cognitive linguistics, particularly metaphors like “number line” or “function machine,” in supporting mathematical thinking. The paper advocates for linguistically responsive teaching, culturally inclusive pedagogy, and equitable assessment practices to enhance learning and promote inclusion. Ultimately, it argues that language is a fundamental tool, not a barrier, for mathematical understanding. While this study provides valuable insights into the intersection of linguistics and mathematics education, it is limited by its reliance on secondary sources and theoretical perspectives rather than empirical classroom-based data.